Penilaian terhadap tahap pembelajaran dan pengurusan program kerjasama UUM-IPTS - Yeon, Asmah Laili; Razalli, Mohd Rizal; Md. Salleh, Salniza; Ahmad, Yuhaniz; Omar, Zurni (2003)
Due to limited placement in Universiti Utara Malaysia (UUM), a lot of qualified students have to find other alternatives to pursue their higher education.The collaborative program between Universiti Utara Malaysia (UUM) and 3 Private Higher Learning Institutes (IPTS) has been conducted to cater those students.The program that has been implemented since 1998 is the Bachelor Degree in Business Administration with Honor (BBA). The main objectives of this paper are to identify whether or not the IPTS abide to the rules and regulation of UUM, to identify whether or not they understand the academic regulations, and to assess the level of teaching among the IPTS lecturers.It is found that two of the colleges conform to the rules and regulations at a satisfactory level.The other college is found to be less satisfactory and its students were also found to be less well-informed to the academic regulations and the aspect of administration of the collaborative program in relation to other colleges.Furthermore, all lecturers in three colleges are found to be effective in counseling and advising their students.These findings will be very useful as guidance for future collaboration between IPTA and IPTS.The suggestions given include the IPTS should be awared with the program agreement while IPTA should always monitor and increase their quality control of the program in order the reduce the gap between IPTA and IPTS.